Потрійні поверхневі комплекси в системах оксид – іони міді – органічний ліганд - Vlasova, N. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
Adsorption of complex copper (II) ions with organic ligands is considered as surface complexation reactions of the oxide – aqueous electrolyte solution interface. Ternary surface complexes at fumed silica surface are formed due to direct interaction of copper ions with silanol groups. In the ternary complexes at titania surface, copper ions are coordinated by a ligand which interacts with functional groups of titania. The equilibrium ternary complex formation constants are calculated from adsorption profiles which reflect the dependence of adsorption values of copper ions and organic ligands on pH.